1994
DOI: 10.1080/07315724.1994.10718452
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hypochlorhydria due to omeprazole treatment or atrophic gastritis on protein-bound vitamin B12 absorption.

Abstract: Omeprazole causes protein-bound vitamin B12 malabsorption, and ingestion of an acidic drink improves protein-bound vitamin B12 absorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(52 citation statements)
references
References 34 publications
0
50
0
2
Order By: Relevance
“…Accordingly, omeprazole interferes with the absorption of vitamin B 12 [80][81][82][83] and protein assimilation [84]. The mechanism for altered vitamin B 12 absorption is prevention of its cleavage from dietary protein [83], for which the importance of the concurrent bacterial overgrowth has not yet been ruled out.…”
Section: Intestinal Microflora In Healthy Individuals With Gastric Hymentioning
confidence: 99%
“…Accordingly, omeprazole interferes with the absorption of vitamin B 12 [80][81][82][83] and protein assimilation [84]. The mechanism for altered vitamin B 12 absorption is prevention of its cleavage from dietary protein [83], for which the importance of the concurrent bacterial overgrowth has not yet been ruled out.…”
Section: Intestinal Microflora In Healthy Individuals With Gastric Hymentioning
confidence: 99%
“…There may also be advantages in terms of dosing (no need for adjustment in renal failure) and in conversion from parenteral to oral forms. It has been demonstrated that long-term use of omeprazole leads to a decrease in serum vitamin B 12 , and monitoring of this should be encouraged [11][12][13]. There is no similar decrease in iron stores [14].…”
Section: Proton Pump Inhibitors: Omeprazole Lansoprazole Pantoprazolementioning
confidence: 96%
“…In spite of prolonged omeprazole therapy associated with cobalamin deficiency due to protein-bound vitamin B 12 malabsorption having been previously described [97], the first case of megaloblastic anemia secondary to vitamin B 12 deficiency was only recently reported by Bellou et al [98] in a patient taking 40-60 mg for 4 years. Omeprazol administration during 4 weeks was also related to a higher incidence of gastric and duodenal bacterial overgrowth secondary to a decreased acid secretion when compared to that observed in a group treated with cimetidine (53 vs. 17%, respectively).…”
Section: Vitamin B 12 Malabsorptionmentioning
confidence: 99%